EDU-WALKING TOUR: MENGOPTIMALKAN PERSONAL BRANDING DESA WISATA DI KAWASAN IKONIK MENARA KUDUS - Pitaloka, Lola Kurnia Pitaloka; Kardoyo, Kardoyo; Saringatun Mudrikah (Universitas Mataram, 2024)
This community service program aims to develop the personal branding of the Menara Kudus area through Edu-Walking Tour. The area’s historical, cultural, and local skills potentials, such as calligraphy craftsmanship and kretek production, have not been fully utilized in existing tourism programs. The Edu-Walking Tour is designed to integrate local historical and cultural stories into the tourism experience, thereby attracting more tourist and empowering the local community. The program includes mentoring for the community and training for tour guides in storytelling skills. Through direct interaction with artisans and community leaders, tourist can gain a deeper understanding of local daily life. The outcomes of this program are expected to enhance the tourist appeal of the Menara Kudus area, boost local economic growth, and preserve the area’s cultural and historical heritage.